Literature Study on Tiktok Social Media as a Marketing Media Tool - Yudhistira, Nurfian; Muflichah, Halla Sayyidah (Sean Institute, 2022)
TikTok has become a new trend in Indonesia, becoming one of the most frequently used social media applications, with more than 100 million monthly active users. TikTok can provide producers and marketing practitioners opportunities as a marketing medium because of the large number of active users. Using literature analysis that focuses on the development of TikTok in the marketing process. So, some conclusions can be drawn. TikTok can build a community; this community has a role in helping influencers reach a wider audience. Through TikTok algorithms, trending hashtags can signal content that they like so that brands have the opportunity to be seen by the audience. Content on TikTok can be created relatively quickly and without a budget. TikTok experiences higher engagement rates from app followers than other social media platforms, as it is more affordable to generate impressions and clicks.